The constructive path of the manager nurse: a grounded theory - Sandra Maria da Cruz Pestana; Maria Manuela Ferreira Pereira da Silva Martins; Cecília Maria Rodrigues (Universidade Federal do Ceará, 2023)
Objective: to understand how nurses experience the succession planning of manager nurses. Methods: qualitative study using grounded theory as a theoretical and methodological reference, with a sample of 20 nurses. Data collection took place through interviews, content analysis, and the conceptual model originated from the coding process. Results: the process of succession planning is informally implemented in the diagnosis of head nurses, but there are some gaps in the systematization of the process. The selection processes, the leadership profile, and experience stand out in the diagnosis, and a casual experience in management is relevant for the preparation of head nurses. Although this is necessary, there are still obstacles, such as the resistance of managers, the turnover of hospital administration councils, and the COVID-19 pandemic. Conclusion: nurses interviewed highlighted many benefits from the planning of succession, but find obstacles to its implementation, which contributes to the reluctance of head nurses to actively participate. Contributions to practice: the theoretical-conceptual model can contribute to change and systematically structure the constructive path of manager nurses, allowing the identification of conditions that promote or limit the diagnosis, education, and development of these professionals.